Design of IoT-based Vehicle Cabin Temperature and Humidity Data Acquisition System - Ridwan, Muhammad; Purwanto, Wawan; Saputra, Hendra Dani; Setiawan, M. Yasep; Abratiguin, Joel O. (AEEJ : Journal of Automotive Engineering and Vocational Education, 2025)
The rising temperature of vehicles in parking lots under the sun is a major cause of poisoning caused by harmful gases in the blood, and the most toxic gas is ammonia (NH3). Exposure to high concentrations of ammonia gas can cause lung damage and death. This research aims to design and build an Internet of Things (IoT)-based vehicle temperature monitoring system using the DHT11 sensor. The DHT11 sensor is able to detect temperature and humidity in real-time with a sufficient level of accuracy, one of the main objectives in the acquisition of temperature data in the vehicle cabin is to improve passenger comfort. Temperatures that are too high or too low can reduce ride comfort. One of the main objectives in the acquisition of temperature data in the vehicle cabin is to improve passenger comfort. Temperatures that are too high or too low can reduce ride comfort. By monitoring and controlling the temperature in the cabin in real-time, the cooling (air conditioning) and heating systems can function more efficiently to maintain the optimal temperature.